Effects of flaxseed supplementation and exogenous hormones on finishing performance, carcass characteristics, and plasma and longissimus muscle fatty acid profiles in finishing cattle - Litton, Leanne Kay (Kansas State University, 2011)
The effects of supplementing forms of flaxseed on plasma and longissimus muscle (LM) fatty acid (FA) composition, finishing performance, and carcass characteristics were evaluated in five studies. In study 1, steers were fed diets with soy oil (SO), ground flaxseed (Flaxseed), or urea formaldehyde condensation polymer treated flaxseed (UFCP). In study 2, steers were fed diets with SO, linseed oil (LO), or a combination of flaxseed and field peas that was extruded (LinPro). Feeding flaxseed products increased (P < 0.01) α-linolenic acid (ALA), omega-3 FA, and decreased (P < 0.01) n-6:n-3 in LM compared to cattle fed SO. Feeding LinPro increased (P < 0.01) ALA, omega-3 FA, and decreased (P < 0.01) n-6:n-3 in LM compared to steers fed SO or LO. In studies 3 and 4, steers were fed diets with and without Flaxseed and implanted or not. Implanting improved (P ≤ 0.05) DMI, ADG, feed efficiency, HCW, and LM area compared to cattle not implanted. In study 4, cattle fed Flaxseed had increased (P < 0.01) ALA and omega-3 FA, and decreased (P < 0.01) n-6:n-3 in LM compared to cattle fed SO. In study 5, heifers were fed diets with 0% or 5% linseed meal, and administered with or without exogenous hormones (NHTC). Administering exogenous hormones improved (P ≤ 0.02) DMI, ADG, G:F, and HCW compared to NHTC cattle. Omega-3 FA increased in LM when cattle were supplemented with flaxseed products. Cattle fed LinPro achieved the highest levels of ALA and omega-3 FA. Flaxseed products did not interact with implants as a natural growth promoter in finishing cattle.
Keywords: Flaxseed; Feedlot; Long chain fatty acids; Growth promotant; Exogenous hormones; Animal Sciences (0475); Biology, Animal Physiology (0433)